Optimizing a therapy for opiate use disorders: Characterizing ondansetron pharmacokinetics in blood and brain - Manhong Wu; Zhuanfen Cheng; Anthony T. Le; Yalun Tan; Gary Peltz (Wiley, 2023)
Abstract Administration of a widely used 5‐hydroxytryptamine receptor (5HT3AR) antagonist (ondansetron) potently inhibited the development of experimentally induced opioid dependence and withdrawal responses in mice and humans. However, in several studies examining withdrawal symptoms in subjects with chronic opioid use disorders (OUDs), ondansetron exhibited reduced or absent efficacy. Because attenuation of opioid withdrawal symptomatology is mediated within the brain, this study examined single‐dose ondansetron pharmacokinetics in the blood and brain of mice. We demonstrate that ondansetron concentrations in the brain (Cbrain ng/mg) are 1000‐fold lower than the blood concentrations (Cblood ng/ml) and decrease rapidly after ondansetron administration; and that a large percentage of brain ondansetron remains in the ventricular fluid. These results indicate that the ondansetron dose, and the time window between ondansetron and opioid administration, and when withdrawal is assessed are critical considerations for clinical studies involving subjects with chronic OUD. The pharmacokinetic results and the dosing considerations discussed here can be used to improve the design of subsequent clinical trials, which will test whether a more prolonged period of ondansetron administration can provide a desperately needed therapy that can prevent the development of neonatal opioid withdrawal syndrome in babies born to mothers with chronic OUD.